Timeliness of Local Government Financial Reporting: Evidence From Indonesia - Gunawan, Andry Wahyu; Arifin, Taufiq (Journal of Governance and Public Policy, 2023)
This research analyzed the determinant of timeliness of local government financial reporting on the financial statements of 508 local governments from 2015 to 2019 financial periods in Indonesia. With secondary data based on the total sampling method, this research used a panel data regression fixed effect model. This study found that financial control and local government revenues positively affected the timeliness of local government financial reporting, local government capital expenditures and the complexity of local governments. Each had an insignificant positive and negative effect on local government financial reporting timeliness. From this study, local governments must increase the capacity of financial supervisors, so the process of financial supervision of local governments can run well, from planning and implementation to reporting on LKPD.